2010
DOI: 10.1111/j.1574-6968.2010.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa and their small diffusible extracellular molecules inhibit Aspergillus fumigatus biofilm formation

Abstract: Aspergillus fumigatus is often isolated from the lungs of cystic fibrosis (CF) patients, but unlike in severely immunocompromised individuals, the mortality rates are low. This suggests that competition from bacteria within the CF lung may be inhibitory. The purpose of this study was to investigate how Pseudomonas aeruginosa influences A. fumigatus conidial germination and biofilm formation. Aspergillus fumigatus biofilm formation was inhibited by direct contact with P. aeruginosa, but had no effect on preform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
175
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 33 publications
5
175
1
1
Order By: Relevance
“…In a clinical setting, various bacterial small molecules have been shown to affect the morphological transition of fungi from the yeast form to the filamentous form, which is critical in the context of fungal pathogenicity. These include short-chain fatty acids from lactic acid bacteria (282) have also been documented; for example, a recent study indicated that diffusible molecules from P. aeruginosa suppress Aspergillus fumigatus biofilm formation in vitro, which may explain why the fungus causes only low mortality in the lungs of cystic fibrosis patients in which P. aeruginosa is a common inhabitant (262). Effects on bacterial and fungal physiology.…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
“…In a clinical setting, various bacterial small molecules have been shown to affect the morphological transition of fungi from the yeast form to the filamentous form, which is critical in the context of fungal pathogenicity. These include short-chain fatty acids from lactic acid bacteria (282) have also been documented; for example, a recent study indicated that diffusible molecules from P. aeruginosa suppress Aspergillus fumigatus biofilm formation in vitro, which may explain why the fungus causes only low mortality in the lungs of cystic fibrosis patients in which P. aeruginosa is a common inhabitant (262). Effects on bacterial and fungal physiology.…”
Section: Consequences Of Bacterial-fungal Interactions For Participatmentioning
confidence: 99%
“…These metabolites could be intermediates in the detoxification process or serve other, as-yet unexplored roles, as exemplified by 1-HP (2), which turned on the production of fungal siderophores. MALDI-IMS also revealed that A. fumigatus converted the P. aeruginosa metabolites PCA (3) and PYO (1) into dimeric phenazines (9,10). The identification of these unique fungal bioconversion metabolites provides opportunities to study their effects on both the producing organism and competing bacterium.…”
Section: Biotransformation Of P Aeruginosa Phenazine Metabolites By Amentioning
confidence: 99%
“…Interestingly, however, in a pulmonary mouse model, mice coinfected with P. aeruginosa and A. fumigatus had a higher survival rate than mice infected by A. fumigatus alone (9). Additional in vitro studies have suggested that P. aeruginosa has an inhibitory effect on filamentation and biofilm formation of A. fumigatus through both direct contact and secreted molecules (10). The coexistence of P. aeruginosa and A. fumigatus in the CF lung, species composition, spatial orientation, and molecular interaction remain to be elucidated, however.…”
mentioning
confidence: 99%
“…One way these organisms interact is through the production and secretion of small-molecule effectors called specialized metabolites, including quorum sensors, virulence factors, and natural products (previously referred to as secondary metabolites) (8,9). In vitro studies show that metabolites secreted by P. aeruginosa inhibit A. fumigatus filamentation and biofilm formation (10). In 2012, we detailed the metabolic interaction between these two microbes, with an emphasis on the A. fumigatus Af293-mediated biotransformation of the phenazine class of specialized metabolites produced by P. aeruginosa PA14 (11).…”
mentioning
confidence: 99%